The mediating role of E-trust in the relationships between E-service quality and E-Satisfaction on Gen Z users Shopee Apps - Martio, Nazmi Ahmad; Mugiono; Wahdiyat Moko (Profesional Muda Cendekia Publishing, 2023)
The aim of this study is to observe the effect of e-service quality on e-satisfaction mediated by e-trust in Shopee application users among generation Z. Excessive trust in users could be capable of growing the resulting sense of satisfaction. User satisfaction may be used by organizations to enhance quality and attract new users. This study is protected in the explanatory research category. Respondents in this look-at have been Shopee application users in Malang city. Identifying the type of samples in this observation used a purposive sampling approach with a sample size of 150 respondents. The record collection method makes use of a questionnaire, and the data are analyzed using PLS-SEM 3.3. The study's outcomes show that e-service quality has a significant impact on e-satisfaction. E-service quality has a significant impact on e-trust, and e-trust has a significant effect on e-satisfaction. e-trust can bridge the mediating position within the courtship between e-service quality and e-satisfaction. It's broadly hoped that the Shopee application can hold and grow user trust, mainly in Gen Z. Keywords: E-service quality; E-satisfaction; E-trust.